Analysis of the Effect of Store Atmosphere and Social Factors on Emotional Responses Affecting Consumers’ Purchase Decision - Dewobroto, Wisnu Sakti; Wijaya, Karen (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Retail is classified as one of the growing industry in Indonesia, but currently it is experiencing a decline in visitors that resulting in the decrease of sales. Retailers or store owners need to find various ways to increase the number of visitors, which can be stimulated by store atmosphere and social factor to create positive emotions that can impact the customer’s purchase decision. Therefore, the study aims to examine the effect of store atmosphere and social factor towards emotional response and its impact to purchase decision. It uses SPSS to test the result of the research. In addition, this study uses non-probability sampling method with the total of 120 respondents who ever visited and shopped at baby equipment retail store at ITC Mangga Dua. The research hypothesis proves that store atmosphere and social factor have no effect and are not individually significant to emotional response, while emotional response individually have significant influence towards customers’ purchase decision. Meanwhile, store atmosphere and social factor through emotional response simultaneously and significantly influence customers’ purchasing decision.